Irish Insanity 1800-2000 : 1800-2000. - Brennan, Damien (Routledge advances in sociology., 2013)
Irish Insanity 1800-2000 charts and explains the rise and demise of asylums and mental hospitals in Ireland between 1800 and 2000. It definitively demonstrates that Ireland had the highest level of asylum usage internationally, arguing that a combination of social forces, rather than an 'epidemic of Irish insanity', underpinned this pattern of institutionalisation.